EXPLORING LANGUAGE BARRIERS DURING INTERNATIONAL TEACHING PRACTICUM IN THAILAND: PRE-SERVICE TEACHERS’ VOICES - Turbinita, Galuh Ellyna; Safriyani, Rizka; Safriani, Afida (J-Shelves of Indragiri (JSI), 2023)
The phenomenon of international teaching practicum exists to accommodate globalization in improving the quality of teaching internationally. However, the phenomenon of global teaching practicum, which has been investigated in many studies,earlier research, raises a number of significant barriers. Hence, this research aims to investigate the barriers faced by the Indonesian pre-service teachers during their teaching abroad program in Thailand. Qualitative research method were chosen in this study in order to obtain in-depth information about the phenomenon of international teaching practice through the interview with three Indonesian pre-service teachers. The findings revealed that Indonesian pre-service teachers discovered and faced several major barriers in the practicum for teaching abroad program in Thailand The toughest challenge experienced by Indonesian pre-service teachers is the language barrier. In addition, the response given by residents and the school environment to the language barriers experienced by Indonesian pre-service teachers was very good. Utilizing how students facilitate communication between Indonesian pre-service teachers and other students, and how in-service teachers offer advice and continue to assist Indonesian pre-service teachers in overcoming language barriers throughout the program.